Histopathology Based Cancer Pattern in Mymensingh Region of Bangladesh - Talukder, SI; Haque, MA; Alam, MO; Huq, MH; Ali, MS; Debnath, CR; Rashid, MM; Roushan, A; Jahan, MK; Nahar, K; Khanom, A (Mymensingh Medical Journal, 2007)
Mymensingh Med J. 2007 Jul;16(2): 165-169The abstract of this article is available on the PubMed website